Information Systems: Modeling, Development, and Integration Third International United Information Systems Conference, UNISCON 2009, Sydney, Australia, April 21-24, 2009, Proceedings - Yang, Jianhua; Ginige, Athula; Mayr, Heinrich C.; Kutsche, Ralf-D (Lecture Notes in Business Information Processing,, 2009)
This volume constitutes the proceedings of the Third International United Information Systems Conference, UNISCON 2009, which was held in Sydney, Australia, during April 21-24, 2009. UNISCON 2009 combines three different events: 8th International Conference on Information Systems Technology and its Applications (ISTA 2009), 8th International Workshop on Conceptual Modelling Approaches for e-Business (eCOMO 2009), and 2nd International Workshop on Model-Based Software and Data Integration (MBSDI 2009). The overall 39 full papers and 14 short papers presented with two keynote speeches were carefully reviewed and selected from 115 submissions. The topics covered are: information systems modelling; information systems analysis; information systems integration; business process modelling; information retrieval and NLP; e-learning and training; datamining, datawarehousing, and visualization; and Web intelligence.